Vascular endothelial growth factor‐C modulates cortical NMDA receptor activity in cortical lesions of young patients and rat model with focal cortical dysplasia. (8th March 2022) - Shen, Kai‐Feng; Duan, Qing‐Tian; Duan, Wei; Xu, Sen‐Lin; An, Ning; Ke, Yan‐Yan; Wang, Li‐Ting; Liu, Shi‐Yong; Yang, Hui; Zhang, Chun‐Qing
Abstract: Emergence of dysmorphic neurons is the primary pathology in focal cortical dysplasia (FCD) associated pediatric intractable epilepsy; however, the etiologies related to the development and function of dysmorphic neurons are not fully understood. Our previous studies revealed that the expression of vascular endothelial growth factor‐C (VEGF‐C) and corresponding receptors VEGFR‐2, VEGFR‐3 was increased in the epileptic lesions of patients with tuberous sclerosis complex or mesial temporal lobe epilepsy. Here, we showed that the expression of VEGF‐C, VEGFR‐2, and VEGFR‐3 was increased at both mRNA and protein levels in patients with cortical lesions of type I, IIa, and IIb FCD. The immunoreactivity of VEGF‐C, VEGFR‐2 and VEGFR‐3 was located in the micro‐columnar neurons in FCD type I lesions, dysplastic neurons (DNs) in FCD type IIa lesions, balloon cells (BCs) and astrocytes in FCD type IIb lesions. Additionally, the amplitude of evoked‐EPSCs (eEPSC) mediated by NMDA receptor, the ratio of NMDA receptor‐ and AMPA receptor‐mediated eEPSC were increased in the dysmorphic neurons of FCD rats established by prenatal X‐ray radiation. Furthermore, NMDA receptor mediated current in dysmorphic neurons was further potentiated by exogenous administration of VEGF‐C, however, could be antagonized by ki8751, the blocker of VEGFR‐2. These results suggest that VEGF‐C system participate in the pathogenesis of cortical lesions in patients with FCD in association with modulating NMDA receptor–mediated currents. Abstract : Shen et al. demonstrate that the expression of VEGF‐C system is increased in the cortical lesions of young patients and rat models with FCD, and participates the epileptogenicity of FCD by modulating NMDA receptor mediated currents.